People and plants - close relationships at the crossroads of the Silk Roads: the case of Tajikistan - Kotowski, Marcin; Świerszcz, Sebastian; Nobis, Marcin; Laldjebaev, Murodbek; Palavonshanbieva, Barfiya; Nowak, Arkadiusz (Ethnobotany Research and Applications, 2024)
Background: This study examines the spatial relationship between human populations, livestock and wild useful plants in Tajikistan, a key area along the ancient Silk Roads. It aims to understand how the distribution of these plants correlates with the presence of humans and livestock. Methods: The study uses statistical analyses, including the LSVM model, to assess the distribution of 4269 plant species, of which 1823 are identified as useful. Various factors such as bioclimatic conditions and plant use categories are taken into account. Results: The results indicate a significant correlation between the distribution of useful plants and human population, especially in urbanised areas, which cover 7.4% of Tajikistan. In particular, flora functionality significantly influences human population distribution. Conclusions: The research highlights the importance of spatial relationships between humans and useful flora in population distribution. It suggests that these relationships should be included in models predicting human settlement patterns based on environmental factors. Keywords: useful plants, human population distribution, Tajikistan, Middle Asia, spatial relationship, ethnobotany, support vector machines, supervised learning models.